Color removal of basic and reactive dyes from simulated textile wastewater by adsorption on corn fiber and biomediated system - Valencia, Sixto A. (2000)
The use of inexpensive adsorbing material such as corn fiber and biomediated system to remove color from the simulated textile wastewater was explored. The biomediated system refers to the combined corn fiber and enriched culture of bacteria in a packed bed bioreactor. The research consists of three parts: (1) physical adsorption method using corn fiber as an adsorbent, (2) biological method using enriched culture of bacteriafor color removal, and (3) combined treatment method using corn fiber and enriched culture of bacteria. The study used four types of dyes basic blue 54 (BB54), basic red 46 (BR46), reactive blue 52 (RB52) and reactive red 120 (RR120).
The first part of the study evaluated the rates of adsorption and the shape of the equilibrium adsorption isotherms of the four dyes on corn fiber. The effects of different temperatures (28°C, 43°C, 60°C) and intial pH levels (5.9, 7.0, 9.0) were investigated. The rates of adsorption for the four dyes were found to vary in the order rBB54>rBR46>rRB52>rRR120. The shapes of the equilibrium adsorption isotherms of the four dyes were best described by Langmuir adsorption isotherm model which indicate high adsorption rates of four dyes on corn fiber at low concentration range. The maximum adsorptive capacities Qmax (mg/g) of corn fiber at an initial pH of 5.0 increased from 434.78, 196.08, 140, and 64.52 mg/g at 28°C to 454.54, 343.57, 166.67, and 102.04 mg/g at 60°C, for BB54, BR46, RB52 and RR120 dyes, respectively. At constant temperature of 28°C the maximum adsorptive capacities of corn fiber increased from 434.78, 196.08, 140, and 64.52 mg/g at pH of 5.0 to 555.56, 344.83, 166.67, and 102.04 mg/g at pH of 9.0, for BB54, BR46, RB52, and RR120 dyes, respectively. Results of the statistical analysis using t-test show that there is a significant difference between the effects of pH (5.0 and 9.0) and pH (7.0 and 9.0) at 5% level of significance. For the effects of temperature, only Qmax at 28°C and 43°C were not significant; the rest of the combinations were signi
The second part of the study used a biological method to remove color from the simulated textile wastewater. A mixture of bacteria, which grew in the experimental flasks during the conduct of the experiment was cultured, isolated and purified. The pure culture of bacteria SV2 was identified and found to be very close to Stenotrophomonas maltophilia with similarity index of 88%. Its growth was evaluated using different substrates (e.g glucose, ammonium acetate, propionic acid, BB54, BR46 dye, BB54 dye plus corn fiber, and BR46 dye plus corn fiber). The effects of initial dye concentration on the percent color removal using an enriched culture of bacteria were investigated. An enriched culture of bacteria was found to be efficient in removing the color of four dyes from the simulated textile wastewater. The time and extent of color removal depended on the volume ratio of dye-to-enriched culture of bacteri
The third part of the study investigated the combined use of corn fiber and enriched culture of bacteria (i,e., biomediated system) in removing the color of four dyes from the simulated textile wastewater. The study determined if the time of treatment to achieve highest percent color removal could be reduced using the biomediated system. The percent color removal with respect to time was calculated. The time at which the biomediated system achieved 96%, 97%, 94% and 86% color removal for BB54, BR46, RB52, and RR120 dyes were 1 day, 1.3 days, 7 days and 8 days, respec
Thesis (Ph.D. Chemical Engineering)--University of the Philippines, Diliman.
Keywords: Color in the textile indu; Abso; Water -- Purification -- Color r; Dyes and dyeing -- Textile f